Clinical study of lurasidone combined with nutritional intervention strategy in the treatment of chronic schizophrenia. (March 2023) - Liu, Hui; Kong, Luya; Yan, Xing; Duan, Dan; Gong, Zhuo
Abstract : Background: Schizophrenia is a complex mental disorder with a chronic course. The atypical antipsychotics represented by lurasidone are commonly used in chronic schizophrenia, and its mechanism of action determines the superiority of efficacy and safety. However so far, there are still some adverse reactions, of which the more significant are lethargy, nausea, and sedentary inability. In view of these situations, we will combine nutrition intervention with the use of lurasidone to eliminate adverse reactions and provide help for the formulation of treatment plans. Subjects and Methods: The study will be based on whether to add nutrition intervention as a difference set up control experiment, the experimental group using lurasidone combined nutrition intervention, the control group using lurasidone single factor intervention. The patients who received treatment in the psychiatric department of our hospital from March 2021 to March 2022 were selected as the research objects, and the efficacy and adverse reactions of the patients were monitored during the treatment. The efficacy will be judged by the medical scale of symptom severity of patients with schizophrenia (Positive and Negative Syndrome Scale, PANSS) and the monitoring data will be statistically analyzed by SPSS. Results: With the treatment, the results of the Experimental group and the control group are shown in Table 1 . The PANSS scores of the two groups finally reached a range of 30-40, with a difference of 4. The incidence of nausea, lethargy and sedentary disorder in adverse symptoms was higher in the control group, and the difference was statistically significant ( P < 0.05). It shows that nutritional intervention cannot affect the efficacy of psychosis itself, yet can alleviate the adverse symptoms after medication. Conclusions: The group of schizophrenics is not limited to a certain age. Therefore, adverse symptoms caused by psychotropic drugs need to be considered in the practice. Symptoms in the course of the patient's disease can be used as a treatment optimization path. Although the nutrition intervention strategy has no direct impact on the indicators of mental illness, the prevention of adverse symptoms during treatment can improve the actual experience of patients. In the future, the nutrition strategy will be adaptively optimized to improve the rehabilitation effect of chronic schizophrenia. Acknowledgements: The research is supported by: Key Discipline of Nutrition and Food Hygiene of Changsha Medical university Quality Engineering Construction Project+2016; Study on Intervention Effect of Mindfulness Acceptance Stress Project on Nurses Aid to COVID-19+Outstanding Youth Project of Scientific Research of Hunan Education Department +2020(264)20B070.